USING VISUAL COMIC STRIPS TO IMPROVE DESCRIPTIVE TEXT WRITING SKILLS OF SEVENTH GRADE STUDENTS AT SMPN MODEL TERPADU MADANI PALU - Balgis Himran; Budi Budi; Desrin Lebagi; Andi Patma Sari (e-Journal of ELTS (English Language Teaching Society), 2026)
The purpose of this study is to determine whether or not the use of visual comic strips is effective to improve the descriptive text writing skills of seventh grade students at SMPN Model Terpadu Madani Palu. The researcher used quasi-experimental research design. The sample consisted of two classes: the experimental group (n = 22), which was taught using Comic Strips, and the control group (n = 22), which received conventional writing instructions methods. An analytical scoring rubric was used to evaluate students' writing abilities. It focused on three areas: mechanics (5 points), organization (35 points), and content (20 points), for a total of 60 points that were converted to a 100-point scale. According to the descriptive statistics, the experimental group improved significantly, with the mean score rising from 41.82 in the pre-test to 85.00 in the post-test, whereas the control group changed very little, from 32.27 to 73.41. A significant difference between the groups was established by the Independent Sample t-test, with an Asymp. Sig. value of 0.001 < 0.05. These results show that comic strips facilitate collaborative work revision and better concept organization for students. Therefore, Comic Strips is effective to improve descriptive writing skills of seventh grade students at SMPN Model Terpadu Madani Palu.